The Celebration - Brunstetter, Wanda E. (Thorndike, Maine : Center Point Large Print, 2018)
"Return to Amish cooking class with Heidi Troyer, when the children she and Lyle are fostering inspire her to teach a series of classes for children. But kids are always accompanied by an adult--and that is where the trouble arises"--
Keywords: Amish -- Fiction; Amish cooking. -- Fiction; Large type books; Christian fiction